2008
DOI: 10.1017/s0014479708006388
|View full text |Cite
|
Sign up to set email alerts
|

Seedling Characteristics and the Early Growth of Transplanted Rice Under Different Water Regimes

Abstract: A series of experiments was conducted on rice seedlings in a nursery seedbed and after transplanting in order to understand root and shoot characteristics, and their contribution to the production of tillers and dry matter. At the nursery stage, the seedlings' were studied at varying densities (high and low) and fertilizer treatments (with and without nitrogen) at 12 and 24 days after sowing (DAS) in wet or dry seedbeds. After transplanting, the effects of seedling age at the time of transplanting (12 and 30 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
51
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(64 citation statements)
references
References 24 publications
(29 reference statements)
12
51
1
Order By: Relevance
“…The positive effect of low seeding density and fertilizer top dressing is of course due to less competition and better plant nutrition, and older seedlings seemed to provide an additional advantage in the drier 2009 season. We did not see a strong effect of fertilizer management in contrast to Mishra and Salokhe, who observed that fertilizer application in the nursery was a crucial factor in increasing seedling vigor [31]. Similarly Farooq et al also found an increasing trend of plant height after transplanting improved nursery seedlings [32].…”
Section: Plant Heightcontrasting
confidence: 79%
“…The positive effect of low seeding density and fertilizer top dressing is of course due to less competition and better plant nutrition, and older seedlings seemed to provide an additional advantage in the drier 2009 season. We did not see a strong effect of fertilizer management in contrast to Mishra and Salokhe, who observed that fertilizer application in the nursery was a crucial factor in increasing seedling vigor [31]. Similarly Farooq et al also found an increasing trend of plant height after transplanting improved nursery seedlings [32].…”
Section: Plant Heightcontrasting
confidence: 79%
“…A shallow depth for Figure 1 Diagrammatic representations of the developmental changes in rice nursling seedlings and the ideal plant ages of nursling seedlings for transplantation (Sasaki 2004). transplanting nursling seedlings could also be favorable for more tillering. Also, biological potential of rice seedlings and their improvement in an oxic nursery environment are suggested for young seedlings (12d old) even they are transplanted to flooded paddy field (Mishra and Salokhe 2008).…”
Section: Young Seedlingsmentioning
confidence: 99%
“…Moreover, the high nitrate content was maintained for more than one month after transplanting and showed the translocation of NO 3 into new roots in the field. Mishra and Salokhe (2008) examined the effect of different water regimes before and after transplanting and showed that nursery water management affected the rate of development after transplanting. They also showed that a dry seedbed was better than a wet seedbed, as the former helps to shorten the phyllochron (period of leaf emergence) and helps produce seedlings with better rooting.…”
Section: Nitrate Its Uptake and Transport And Effect On Growth Of Rmentioning
confidence: 99%
“…Pakistan earned US$ 1.53 billion in rice exports and it contributes 3.2% in the value addition in agriculture and 0.7% of GDP [7]. Every day increasing urbanization and population in cities and villages increases the demand and consumption of rice worldwide [8].…”
Section: Introductionmentioning
confidence: 99%